Itinéraires et mutations urbaines dans le Mašriq islamique (Ier/VIIe-IIIe/IXe siècles) - Bessard, Fanny (Arabica, 2017)
In the 1st/7th and the early 2nd/8th centuries, the Arab-Muslim conquest united two immense territories, once separated by a shifting border joining the Black sea to the Persian Gulf. To the East, the Arab-Muslims dominated Central Asia and the long-held Asian empire of the Sassanids that reached as far as the Chinese and Indian borders. To the West, they controlled the southern part of the Eastern and Western Roman empires. In the 2nd/8th century, the area conquered thus formed a narrow belt of lands from the Atlantic to the Chinese borders and from Georgia to Yemen. The Middle East became a converging hub of merchants and commercial goods. The article aims to discuss the political and social mechanisms involved in redrawing the map of the routes in the Mašriq from the early Umayyads in 41/661 to the death of caliph al-Muktafī in 295/908. It investigates the impact the evolution of road networks had on settlement patterns and economic strategies.